Drought, sustenance and livelihoods: `Akal" survey in Rajasthan - Sivakumar, Sowmya; Kerbart, Eric (2004)
This article presents findings from a survey conducted in Rajasthan in March-April 2003, when the `maha akal', the drought, was at its peak over large parts of rural Rajasthan and the government-initiated relief works were yet to make an impact. Covering 122 hamlets in 56 panchayats across nine districts, the report examines the manifestation of drought in people's everyday lives - specifically the ways food and water shortages impact men, women and children. It also examines the long-run impact of drought on people's assets and livelihoods and the coping strategies they adopt. - Reproduced.
Keywords: Drought - India - Rajasthan; Drought